Effect of Different Nutrient Sources Including Sewage Sludge on Growth Performance and Carbon Sequestration Potential of Melia azedarach and Eucalyptus tereticornis Plantations: Effect of sewage sludge on growth of trees - Singh, Baljit; Kaur , Harmandeep; Thakur, Sapna (Journal of Soil Salinity and Water Quality, 2025)
The present study evaluates the impact of different nutrient source including sewage sludge on the growth performance, productivity and carbon sequestration by Melia azedarach (dek) and Eucalyptus tereticornis (eucalyptus) plantations. The trees were planted at a spacing of 4 x 3 m i.e., 833 trees ha-1 in randomized block design (RBD) in three replications with a net plot size of 4 plants plot-1. The treatments viz. T1: recommended dose of nitrogen (N) and phosphorus (P) through inorganic fertilizers (urea and DAP), T2:100% N through farmyard manure (FYM), T3:100% N through sewage sludge, T4: 50% N through sewage sludge and T5:150% N through sewage sludge were applied. Growth measurements, including diameter at breast height (DBH) and height, were recorded annually and timber volume was estimated using species-specific regression equations. At six years of age, total biomass production, carbon stock and carbon dioxide (CO₂) assimilation potential were also quantified. Statistically significant variations were observed among treatments for both species across the years. In dek, DBH, height and timber volume were 10.7, 14.4 and 33.2% higher, respectively in T2 over T4 with recorded ranges of 17.17–19.01 cm, 16.71–19.12 m, and 188.8–251.4 m³ ha⁻¹, respectively. Similarly, in eucalyptus, T2 had 8.7, 6.7 and 34.8% higher DBH, height and volume, respectively over T4 with corresponding ranges of 18.87–20.50 cm, 23.02–24.56 m, and 182.6–246.1 m³ ha-1, respectively. Consequently, T2 also resulted in the highest total biomass (270.6 and 242.8 Mg ha-1), total carbon stock (123.5 and 110.8 Mg C ha⁻¹) and CO₂ assimilation potential (453.1 and 369.2 Mg CO₂ ha⁻¹) in dek and eucalyptus, respectively. The findings demonstrate that the growth and productivity of both species under T2 and T3 were statistically better compared to other treatments. Therefore, sewage sludge can be effectively utilized as an alternative organic nutrient source for enhancing the productivity and carbon sequestration potential of Melia and Eucalyptus plantations instead of inorganic fertilizers.